Causes and Risk Factors for 30-Day Unplanned Readmissions After Pediatric Spinal Deformity Surgery. Issue 4 (15th February 2015) - Martin, Christopher T.; Pugely, Andrew J.; Gao, Yubo; Weinstein, Stuart L.
<x xml:space="preserve">Abstract</x> Study Design. Retrospective review of a prospective cohort. Objective. To determine the incidence, risk factors, and causes for 30-day unplanned readmission after pediatric spinal deformity surgery. Summary of Background Data. The government has targeted 30-day readmissions as a quality of care measure. However, few studies have analyzed readmission in pediatric cohorts. Methods. A multicenter registry designed to collect pediatric surgical outcomes was queried for patients undergoing spinal deformity surgery in 2012. Patients were divided into groups of those with and without an unplanned readmission within 30 days postoperatively. Univariate and multivariate logistic regression analyses were used to compare the cohorts, and to identify variables associated with readmission. Results. In total, 75 of 1890 pediatric patients undergoing spinal fusion for deformity had an unplanned 30-day readmission (3.96%). Readmissions were highest in the neuromuscular group (6.83%) and lowest in the idiopathic (2.66%) and infantile (1.31%) cohorts, (P < 0.01). The top reasons for readmission included wound complications (73.3%) and gastrointestinal disturbances (13.3%). In the univariate analysis, increasing surgical complexity, particularly fusions to the pelvis and isolated anterior spinal fusions, as well as increasing medical comorbidity burden were each associated with readmission (P < 0.05 for each). In the subsequent multivariate analysis, isolated anterior spinal fusions (odds ratio, 7.65; 95% confidence interval, 1.32–44.3) structural pulmonary abnormalities (odds ratio, 2.53; 95% confidence interval, 1.22–5.23) and an American Society of Anesthesiologists class of 3 or 4 (odds ratio, 2.18; 95% confidence interval, 1.07–4.47) were independently associated with readmission. Conclusion. The overall rate of 30-day unplanned readmissions after pediatric deformity surgery was low, but not insignificant. Surgeons should consider discharge optimization in the at-risk patient cohorts defined here, and should focus on wound complications and gastrointestinal disturbances to minimize readmissions. Quality reporting metrics should incorporate these risk factors to avoid unduly penalizing surgeons who take on complex cases. Level of Evidence: 3